Iris recognition using convolutional neural network / Zhuang Yuan - Zhuang, Yuan (2018)
This research aims at designing a practical system to recognize and classify human’s iris. Iris recognition is an advanced technology that is being actively researched for many decades and is gaining wider popularity. The rising of artificial intelligence provides a great opportunity to further popularize iris recognition. Convolutional neural network is a practical algorithm that is highly suitable for image processing and pattern recognition, its effectiveness and flexibility allows it to be used in many fields. This study focuses on building a system of iris recognition based on convolutional neural network, that is able to recognize human’s eyes precisely and efficiently.